2022
DOI: 10.3389/fimmu.2022.850846
|View full text |Cite|
|
Sign up to set email alerts
|

Definition of the Immune Parameters Related to COVID-19 Severity

Abstract: A relevant portion of patients with disease caused by the severe acute respiratory syndrome coronavirus 2 (COVID-19) experience negative outcome, and several laboratory tests have been proposed to predict disease severity. Among others, dramatic changes in peripheral blood cells have been described. We developed and validated a laboratory score solely based on blood cell parameters to predict survival in hospitalized COVID-19 patients. We retrospectively analyzed 1,619 blood cell count from 226 consecutively h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…Using lymphocyte and granulocyte-related parameters to build the model can well predict the disease severity and survival of COVID-19 patients. With the optimal cut-off score of 30.6 obtained by ROC curve, the sensitivity and specificity of detection were 82.0% and 82.5%, respectively ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Using lymphocyte and granulocyte-related parameters to build the model can well predict the disease severity and survival of COVID-19 patients. With the optimal cut-off score of 30.6 obtained by ROC curve, the sensitivity and specificity of detection were 82.0% and 82.5%, respectively ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, both the increased levels of L depletion and marked perturbations in L subset composition might be important factors leading to exacerbations of patients, while the recovery of L numbers helped to alleviate the severity of disease 36 . Likewise, it has been reported that a laboratory score derived from lymphocyte‐ and granulocyte‐associated parameters reflected and anticipated the disease gravity, urgent need for ICU admission, and chances of survival of hospitalized SARS‐COV‐2 patients 37 . LDC‐related parameters expands clinicians' ability to personalize risk assessment and management opinions for patients.…”
Section: Discussionmentioning
confidence: 99%
“…36 Likewise, it has been reported that a laboratory score derived from lymphocyte-and granulocyte-associated parameters reflected and anticipated the disease gravity, urgent need for ICU admission, and chances of survival of hospitalized SARS-COV-2 patients. 37 LDC-related parameters expands clinicians' ability to personalize risk assessment and management opinions for patients. During the early stage of viral infection, depletion efficiencies of some proteins increased via participating in antiviral response against viral invasion and replication, whereas levels of some acute phase proteins in plasma such as CRP, might be elevated.…”
Section: Pcamentioning
confidence: 99%
“…Globally, as of September 2022, there were 613 million confirmed COVID-19 cases, resulting in 6.5 million deaths, reported to the World Health Organization (WHO) [ 1 ]. To properly manage the hospitalization of COVID-19 patients, it became obvious that the methods to assess the severity and outcome of the disease, such as the distribution of cell types and the viral infection in peripheral blood, were very important [ 2 ].…”
Section: Introductionmentioning
confidence: 99%